Effect of Ralgro and Compudose on grazing steer performance - Lomas, Lyle W. (Kansas State University. Agricultural Experiment Station, 2011)
COMPUDOSE (an estradiol removable implant) increased steer gains during 202 days of grazing by 11.4%. Ralgro implants (once at the beginning of the study) increased gain 8.5%. Steer performance on the two implants was statistically similar.
Keywords: Beef; Ralgro; Compudose; Steer performance